How a river submerges into the sea: a geological record of changing a fluvial to a marine paleoenvironment during early Holocene sea level rise - Hepp, D. A.; Romero, O. E.; Moerz, T.; De Pol Holz, Ricardo Hernán; Hebbeln, D. (My University, 2019)
Coastal seas, and in particular estuarine systems, were significantly affected by Quaternary sea level changes. Furthermore, the dynamics of shelf and coastal evolution have had a strong impact on coastal landscapes inhabited by humans. The postglacial evolution of the vast North Sea shelf with its huge drainage systems, e.g. the Elbe Paleovalley and its tributary system, is an excellent research target to understand how coastal shelf environments change in response to sea level rise. In this study, we investigate infill sediments of the Paleo-Ems valley - a drowned extension of the modern Ems River and part of the Elbe Paleovalley drainage system. Radiocarbon-dated transgression sequences provide several new observations regarding the mode and rate of the river system submerging due to the Holocene transgression. Thus, the Paleo-Ems valley submerged within a short time span of similar to 200 years since the river was not able to adjust its gradient to the rapid rising sea level. The fate of the Paleo-Ems is exemplary for the rapid change of a former fluvial landscape into a coastal landscape and finally into a submarine seascape.
Keywords: coastal evolution; holocene transgression; paleolandscape; submerged river